1984
DOI: 10.1159/000225862
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of the Upper Urothelial Tumours in a Family

Abstract: In a Balkan nephropathy endemic area, 5 siblings developed haematuria over a period of 10 years. 4 of them were operated on and pathohystological examination revealed papillary transitional cell tumours of the renal pelvis and/or ureters. Both these tumours and the Balkan nephropathy affected only 1 generation of the family members. This fact, as well as the other relevant evidence, indicated that environmental factors played an important role in the process of carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Frequency of UUT is very high in BN endemic foci [3,8,9], with an occasional extreme clustering of this rare malignancy within a family [10]. Lesions are often multifocal and bilateral [5,7], and pathohistology reveals transitional cell tumors [2], Data on survival of UUT patients from BN endemic areas are scanty, controversial and either methodologi cally dubious [1] or nonnumerical [5,7], This was the reason why we attempted to compare the survival of UUT patients from BN endemic and nonendemic re gions.…”
mentioning
confidence: 99%
“…Frequency of UUT is very high in BN endemic foci [3,8,9], with an occasional extreme clustering of this rare malignancy within a family [10]. Lesions are often multifocal and bilateral [5,7], and pathohistology reveals transitional cell tumors [2], Data on survival of UUT patients from BN endemic areas are scanty, controversial and either methodologi cally dubious [1] or nonnumerical [5,7], This was the reason why we attempted to compare the survival of UUT patients from BN endemic and nonendemic re gions.…”
mentioning
confidence: 99%
“…Upper tract urothelial tumors were 57 and 62 times more frequent in villages where Balkan nephropathy is endemic than in neighbor ing nonendemic villages and cities, respectively [62]. This study has shown that not only tumors of the renal pelvis and ureter but also urinary bladder tumors are up to 8.5 and 11.9 times, respectively, more frequent in endemic settlements [62], An increased incidence of UTT was observed in the families of patients with Balkan nephropathy [58,[63][64][65]. In endemic settlements, tumors of the renal pelvis and ureter were 5 times, those of the urinary bladder 7 times more frequent in families with Balkan nephropa thy than in those free of nephropathy, and up to 224 times more frequent than in city families [62],…”
Section: Balkan Nephropathy and Urothelial Cancermentioning
confidence: 99%